Antipsychotic initiation and new diagnoses excluded from quality‐measure reporting among Veterans in community nursing homes contracted by the Veterans Health Administration in the United States. Issue 1 (5th November 2021) - Moyo, Patience; Corneau, Emily; Cornell, Portia Y.; Mochel, Amy L.; Magid, Kate H.; Levy, Cari; Mor, Vincent
Abstract: Objectives: To assess whether prevailing antipsychotic use rates in community nursing homes (CNH) influence new initiation of antipsychotics and diagnosis with antipsychotic indications among Veterans. Methods: We used linked 2013–2016 Veterans Administration (VA) data, Medicare claims, Nursing Home Compare, and Minimum Data Set (MDS) assessments. The exposure was the proportion (in quintiles) of all CNH residents prescribed antipsychotics in the quarter preceding a Veteran's admission date. Using adjusted logistic regression, we analyzed two outcomes measured using MDS: antipsychotic initiation, and new diagnosis of an antipsychotic quality‐measure exclusionary condition (i.e., schizophrenia, Tourette's syndrome, or Huntington's disease). Results: Among 8201 Veterans without an indication for antipsychotics at baseline, 21.1% initiated antipsychotics and 3.5% were newly diagnosed with any exclusionary diagnosis after CNH admission. Schizophrenia accounted for almost all (96.8%) the new diagnoses. Antipsychotic initiation increased with higher CNH antipsychotic use rates: OR = 2.55, 95% CI: 2.08–‐3.12, quintile 5 versus 1. CNHs with the highest prevalent use of antipsychotics were associated with increased odds of Veterans acquiring an exclusionary diagnosis (OR = 2.09, 95% CI: 1.32–3.32, quintile 5 vs. 1). Conclusions: Incident antipsychotic use is common among Veterans admitted to CNHs. CNH antipsychotic prescribing practices are associated with Veterans being newly diagnosed with antipsychotic prescription indications, primarily schizophrenia.